A Narrative Review: The Use of the Topical NSAID Ibuprofen for the Treatment of Knee Osteoarthritis. Supporting Clinician Decision-Making in the First-Line Treatment of Osteoarthritis. (June 2020) - Hawthorn, Catrin
A Narrative Review: The use of the topical nonsteroidal anti-inflammatory drugs (NSAID) ibuprofen for the treatment of knee osteoarthritis. Supporting clinician decision-making in the first-line treatment of osteoarthritis. Objective: To open discussion at a clinical level on the guidelines for the pharmacological management of osteoarthritis of the knee, this narrative review looks into the use of topical NSAID being a clinically effective, safe, and cost-efficient treatment compared to an oral alternative. Background: With the over prescription of NSAIDs in the age of above 65 years, there has been a call for increased restrictions of the sale of oral preparations of NSAIDs. It is our view that there is still a lack of awareness in the benefit of topical NSAIDs to the patient (no evidence of adverse reactions recorded by the Joint Formulary Committee [JFC] to date) as well as provider (topical application is cheaper as a National Health Service [NHS] prescription). Methods: Key online resources included PubMed, Athens, Cochrane Library, Google Scholar, MEDLINE, and relevant clinical and commissioning guidelines with the final date of data collection in March 2017. We also contacted the manufacturer and license holder directly for further clarification. Randomized, double-blind control studies, commissioned reports, International Guidelines, MEHA Guidelines, and license holder data were included. Where possible studies included had to have fair randomization and adhere to key treatment pathways as highlighted by National Institute for Health and Clinical Excellence (NICE) and other guidelines. Discussion: Current guidelines advise that patients who seek initial treatment of osteoarthritis of the knee should consider a combination of treatment modalities, including pharmacological therapies, particularly the use of NSAIDs. At a clinical level, a reoccurring issue identified with this advice is the inappropriate use of oral NSAIDs, and the concern that the risks associated with ease of access ("over the counter"), and overuse, may result in systemic adverse events in this cohort of patients. Multiple studies have examined the negative effect of oral NSAIDs and the associated risks of use. We were unable to source studies that showed any adverse systemic events from the use of topical NSAIDs; however, there are good quality trials comparing oral to topical NSAIDs, showing similar levels of efficacy at 6 and 12 weeks. Conclusion: Topical NSAIDs provide good levels of pain relief in subjects with mild to moderate knee osteoarthritis. There is also evidence for the use of the topical application being a clinically effective, safe, and cost-efficient treatment.